Exploring agency, communion and narrative foreclosure in cognitive behavioural therapy for substance use disorders - Mark de Lange; Job van der Palen; Hein de Haan (Addictive Behaviors Reports, 2025)
Introduction: Substance use disorders (SUDs) are a significant societal concern, negatively impacting self-worth, hope, and interpersonal connectedness. SUD recovery involves a transformation of one’s ‘life-story’ or ‘narrative identity’. ‘Narrative foreclosure’ (NF) impedes this process by disconnecting past, present, and future narratives, hindering the rewriting of SUD-related identities. We investigate the impact of SUD-based cognitive behavioural therapy (CBT) on narrative identity transformation and hypothesise NF as a potential factor in post-treatment relapse. Methods: 107 patients referred to an outpatient clinic for adults with SUDs in the Netherlands were included. Participants completed the “Agency and Communion Inventory” (translated and validated in Dutch), the Narrative Foreclosure Scale (NFS) and the “Measurement of Addiction for Triage and Evaluation” (MATE), including the Depression, Anxiety, and Stress-Scale (DASS-21). Data collection occurred at the start of treatment, post-treatment (+3 months), and during a follow-up measure (+6 months). Results: While participants showed a substantial reduction in substance use frequency and DASS-21 sum scores during CBT-treatment, no such differences were found in narrative themes. Multivariate models revealed that baseline communion and past-directed NF predicted ’substance-use reduction’ during treatment, while ’cannabis use,’ communion and future directed NF were predictors of ’DASS-21 sum score reduction’. Baseline communion showed a moderate positive relation to post-treatment relapse, while ’NFS: Future’ exhibited a moderate inverse relation. These findings remained robust even when altering the criteria for defining ’post-treatment relapse.’ They indicate that a stronger identification with communal themes serve as a protective factor against relapse, while future directed NF is associated with higher relapse rates. Conclusion: this study provides valuable insights into the interplay between narrative themes and treatment outcome(s) in SUD recovery. Notably, our findings underscore the significance of future-directed narrative foreclosure in the recovery process and found that CBT for SUDs does not appear to significantly facilitate narrative identity transformation. These results suggest that existing addiction treatments could be enhanced through the integration of narrative-focused interventions.